KAJIAN PEMIKIRAN EKONOMI : PERBEDAAN PANDANGAN AL GHAZALI DAN ADAM SMITH TENTANG MEKANISME PASAR - Amelya Romawati; Kamilah Khumairoh, Jalaluddin I.R, Renny Oktafia (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
A country's economy is largely market driven. Market success can be seen through ideal mechanisms, which maintain justice and freedom. Economists who view markets as a mechanism for setting prices are the ones who came up with the concept of market mechanisms. The aim of this research is to compare the perspectives of conventional and Islamic economic figures regarding market mechanisms. To obtain a theoretical basis for this research, the approach used in this research is library research, which involves collecting and reviewing various reference materials and the results of similar previous research. Al-Ghazali's free market philosophy is in accordance with Islamic moral and ethical standards, whereas according to Adam Smith the free market philosophy is based on rationalism and individualism. Al-Ghazali's analysis uses a historical approach in his thinking, while Adam Smith uses logical skills in his thinking